Effect of an unusual source of methionine on the performance of organic chickens - Demattê Filho, Luiz Carlos; Pereira, Dayana Cristina de Oliveira; Pereira, Gustavo do Valle do; Beutner, Christian Güdde [UNESP] (Springer Nature, 2016)
The use of amino acids from alternative sources to reduce costs and increase or maintain poultry production levels is crucial to succeed in competitive industry. This study investigated the alternative methionine effects obtained from soybean compared to synthetic DL-methionine—99 % on the broilers performance in the production periods of 1–21 and 1–42 days of age. A total of 720 pullets were included in a completely randomized design with four treatments and six replicates of 30 birds. They received water and food ad libitum throughout the production phase. Diets consisted of T1—reference diet formulated with synthetic methionine (DL-methionine—99 %); T2—diet replacing 100 % of synthetic methionine with alternative methionine; T3—diet replacing 110 % of synthetic methionine with alternative methionine, and T4—diet replacing 120 % of synthetic methionine with alternative methionine. At 1–21 days of age, there was a significant difference (p < 0.05) among treatments in daily gain weight (DWG), live weight (LW), and feed intake (FI). However, no differences were observed (p > 0.05) in feed conversion (FC) and mortality rates. At 42 days of age, a significant difference (p < 0.05) in DWG, LW, and FC parameters was observed among treatments, but there were no differences in FI and mortality. Broilers supplemented with alternative methionine showed significantly lower DWG, LW, FI, productive efficiency index (PEI), and flock uniformity (FU) and showed higher FC compared to animals supplemented with synthetic methionine. The synthetic methionine replacement resulted in lower broiler performance. More researches are necessary to promote better alternative diets for this system.
Keywords: Alternative feed source; Broiler chickens; Methionine; Organic system